ANALYSIS OF FACTORS AFFECTING INTEREST IN SAVING IN ISLAMIC BANK: KNOWLEDGE, SOCIAL ENVIRONMENT AND PSYCHOLOGICAL FACTORS - Iin Emy Prastiwi; Muhammad Naufal Zuhdi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Lack of knowledge of prospective customers about the ins and outs of the Islamic bank system has an impact on changes in interest in saving, which initially intended to save in Islamic banks changed to conventional banks. So far, prospective customers think that saving at conventional banks is simpler than Islamic banks, because Islamic banks themselves prioritize the halal of all transactions carried out and keep away from the name of the usury system. This is what causes the change in the mindset of prospective customers in making decisions about determining where he will raise funds. This study aims to see the extent of the influence of knowledge, social and psychological environment of students on saving interest in Islamic banks. The method in collecting data in this study was through distributing questionnaires to Al Muayyad Islamic Boarding School graduates. The results of this study indicate that knowledge, social and psychological factors together have a significant effect on students' interest in saving in Islamic banks, partial results indicate that knowledge and psychology have a significant effect, while the social environment has no significant effect.